Maternal Educational Practices: Difficulties in Early and Middle Childhood - Reis, Aline Henriques; Daolio, Carla Cristina; Neufeld, Carmem Beatriz (Journal of Psychology and Psychotherapy Research, 2014)
The family is the system that most influences a child’s development throughout different phases. The perceptions of parents about skills, abilities, and characteristics of each developmental stage influence the way they will behave with their children. Objectives: To identify the main difficulties found by mothers in the education/upbringing of children in early childhood (3-6 years) and middle childhood (6-12 years). Method: Participants were 120 mothers (two groups of 60 mothers for each age range), mostly married, ranging in age from 30.4 to 36.5 years, who completed a self-administered questionnaire containing essay and multiple-choice questions about data on characterization of the sample and maternal difficulties in dealing with their children according to the child’s stage of development. Participants completed the questionnaires at home or in schools. Results: More than 75% of mothers live with their child’s father, and more than 78% of these fathers help in child-rearing activities. Mothers spent an average of more than 4 hours a day with their children. Major difficulties of mothers of children in early childhood: putting toys away (63.3%), obedience to maternal commands (46.7%), sleeping on schedule (43.3%), eating an adequate diet (40%). Major difficulties of mothers of children in middle childhood: eating an adequate diet (43.3%), sleeping on schedule (41.7%), putting toys away (38.3%), and obedience to maternal commands (36.7%). Conclusion: The data show an increasing difficulty by mothers in getting children to do their homework and to learn school content as the child’s age advances. Common difficulties are centered on the establishment of a routine and obedience.